¡Vamos! Let's go eat! - Raúl the Third, 1976- (Houghton Mifflin Harcourt, 2020)
Little Lobo, a Mexican American, and Bernabé, his dog, gather tacos, frutas picadas, cuernos, and more and deliver them to los luchadores preparing for Lucha Libre 5000.